"There's no off-switch for us:" Head Start family engagement amidst COVID-19. (June 2022) - Callie Silver, H.; Coba-Rodriguez, Sarai
Highlights: Illinois Head Start programs refocused their attention from in-person events to supporting caretakers in at-home learning activities during the pandemic. Centers used more variable communication strategies and technologies to reach families. Providing resources to meet families' basic needs was an important entry point to building relationships. Being flexible, responsive, and meeting families where they were at continued to be critical for successful family engagement. Abstract: Head Start center closures as a result of the COVID-19 pandemic required providers to innovate to continue engaging families and building relationships. Family Engagement has long been a pillar of Head Start's holistic approach to working with children and families in poverty. The present study provides a unique qualitative, longitudinal perspective of 20 Illinois-based Head Start/Early Head Start center directors regarding their engagement and communication strategies with families prior to, during, and after state-mandated center closures. Findings indicate that staff developed novel approaches to working with families within the context of COVID-19, some of which may have an important place in a post-pandemic world.